2021
DOI: 10.1136/jim-2020-001459
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 levels and the prediction of atrial high-rate episodes in patients with cardiac resynchronization therapy

Abstract: Galectin-3 is an inflammation biomarker associated with atrial remodeling which plays a role in the development of atrial fibrillation (AF). Atrial high-rate episode (AHRE) is related to development of clinically documented AF and stroke. The present study aimed to determine the relationship between the presence of AHRE and the coronary sinus (CS) serum sampling of galectin-3 levels in the long-term follow-up of cardiac resynchronization therapy (CRT) patients. A total of 108 consecutive CRT patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…According to Aksan et al, CRT patients who had high galectin-3 levels were more likely to develop AHREs [12]. However, although Gal-3 was not identified as an independent predictor in our study's multivariate analysis, it was related with a higher risk of developing AHREs in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…According to Aksan et al, CRT patients who had high galectin-3 levels were more likely to develop AHREs [12]. However, although Gal-3 was not identified as an independent predictor in our study's multivariate analysis, it was related with a higher risk of developing AHREs in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…Nonetheless, the study did not demonstrate that elevated Gal-3 serum concentration was associated with prevalent AF in the HF population. The opposite result was shown in the prospective study by Aksan et al in HF patients undergoing CRT [133]. The study revealed that Gal-3 serum concentration was significantly higher in patients with atrial high-rate (AHR) episodes, which were related to AF than in those without AHR episodes.…”
Section: Heart Failure With Atrial Fibrillationmentioning
confidence: 74%